Development of a spectrophotometric analytical approach for the measurement of cefdinir in various pharmaceuticals - Ali Khalil Mahmood; Takleef Dheyab Sallal; Khalid Waleed S Al-Janabi; Hasan Mohammed Luaibi (Wolters Kluwer Medknow Publications, 2023)
An accurate and sensitive determination procedure has been established for the quantification of cefdinir in pure and pharmacological formulas. The approach was dependent on derivatizing cefdinir with sodium anthraquinone-2-sulfonate (SAS) in an alkaline medium to produce a magenta-colored derivative with a maximum absorbance at 517 nm against the reagent blank. Different factors affecting the interaction of cefdinir with SAS were studied carefully and optimized, such as the buffer value, medium acidity, the duration of hydrolysis, and the reagent percentage. Under optimized conditions, a linear calibration curve with a correlation coefficient of R2 = 0.9995 was obtained over the concentration range of cefdinir 0.5-100 μg/mL. The values of the parameters that represented the sensitivity of the method were satisfactory, i.e., the limit of detection, the limit of quantification, as well as Sandell's sensitivity (л) were 0.1 μg/mL, 0.5 μg/mL, and 0.064 μg/cm2/0.001 Au, respectively. The relative standard deviation was below 1.35%, while the percentage recovery was 99.930%-102.257%. The mole ratio of the colored complex was estimated by following Job's method of continuous variation, which indicated that the cefdinir-SAS ratio was 1:1. The suggested approach was proven to be adequately accurate, precise, and without interfering with common excipients and additives. Thus, it could be implemented successfully for the standard determination of cefdinir in its pure and pharmaceutical forms.